The relationship between social media context awareness and active coping during COVID-19: the mediation effect of positive reframing - Rad, Dana; Rad, Gavril (Technium Social Sciences Journal, 2021)
Awareness of the context of social media is identified as an emerging technical capacity relating to the awareness of the social digital community in which a particular experience takes place, realizing the impact on the observer of the perceived social media context, rationalizing the process of social media information undergoing and owning trust for acting on social media. This investigation is an explorative research, analyzing data form 403 Romanian respondents in an online survey, regarding the psychological effect of the imposed social isolation, over respondent’s coping mechanisms. We used the Brief-COPE to determine efficient and inadequate ways to deal with adverse situations and the 4 items SMCA social media context awareness scale. The hypothesis is that the association between social media context awareness (SMCA) and active coping (AC) is mediated by positive reframing (PR), as a potential enhancer of active coping under prolonged social isolation periods over the general population. The standardized indirect effect found was (.11) × (.37) =.04, supporting the mediation hypothesis, suggesting that rather than a direct causal relationship be-tween the SMCA and the AC, our mediation model proposes that SMCA influences the PF mediator variable, which in turn influences the dependent variable AC. Social media context awareness along with positive reframing as a mediator, in a stressful situation, are enhancers of an active coping mechanism.